Design of Intelligent Predictive Model for Ionospheric Disturbance in IRNSS - Manaswini , R.; Raju, G. (International Journal of Intelligent Systems and Applications in Engineering, 2023)
The Indian regional navigation satellite system is one of the important missions of ISRO which will mainly concentrate in providing real précised position and timing information. Ionosphere is a important layer of Earth’s atmosphere that effect the electromagnetic signals that is transmitted and received between satellite and user introduces the error in position determination. The delay induced by ionosphere is iono delay higher the delay more will be total electron content and vice versa. Increased Iono delay and total electron content will indicate more error in position determination. A predictive model for IRNSS receiver is implemented which will estimate these factors. The data of different days are used to study the variation of ionosphere over Bangalore region using real time data of IRNSS. The study includes the accuracy determining parameter called DOP dilution of precision which has decreased as the number satellites increased which is the sign of higher accuracies of IRNSS.